2003
DOI: 10.1088/0953-8984/15/3/305
|View full text |Cite
|
Sign up to set email alerts
|

Phase coexistence in a DLVO model of globular protein solutions

Abstract: Globular protein solutions of lysozyme in water and added salt are modelled according to the Derjaguin–Landau–Verwey–Overbeek (DLVO) theory, in order to determine their fluid–fluid and fluid–solid coexistence lines. Calculations are based on both computer simulations and theoretical approaches. Our results indicate that, when the potential parameters are obtained by fitting physical properties directly deducible from either static or dynamic light scattering data, the fluid–fluid phase coexistence predictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…(13)]. Recently Ruzicka et al [85] have suggested that at low concentrations the effective interaction between Laponite platelets are characterized by a competition of long-range Coulomb repulsion and short-range van der Waals attraction similar to colloidal systems and protein solutions [86,87,88]. Moreover, the charge density is higher on the face than on the rim of a platelet, which leads to a modification of the interaction potential between sites on particles i and j [Eq.…”
Section: B Effective Interaction Potentialmentioning
confidence: 99%
“…(13)]. Recently Ruzicka et al [85] have suggested that at low concentrations the effective interaction between Laponite platelets are characterized by a competition of long-range Coulomb repulsion and short-range van der Waals attraction similar to colloidal systems and protein solutions [86,87,88]. Moreover, the charge density is higher on the face than on the rim of a platelet, which leads to a modification of the interaction potential between sites on particles i and j [Eq.…”
Section: B Effective Interaction Potentialmentioning
confidence: 99%
“…These studies have proven that spherical structures can lead to a curvature-induced enhancement of the amount of polymers adsorbing on top of the spherical structures when appropriate bead sizes were chosen [22]. Since proteins in contrast to most other simple polymers have a well-defined, 3D configuration of minimal energy with a highly complex structure, only a crude understanding of how proteins might behave on nano-structured surfaces can be established from such model studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, colloids appear to be ideal systems for unraveling the physics of gel formation. Understanding the key features of the interaction potential that stabilize the gel phase will probably have an impact also on our understanding of the protein crystallization problem [11,12], where the possibility of generating crystal structures is hampered by the formation of arrested states.…”
Section: Introductionmentioning
confidence: 99%